Journal of Economic Interaction and Coordination - Lux, Thomas; Chen, Shu-Heng.; Iori, Giulia; SpringerLink (Online service) (Berlin/Heidelberg : Springer Berlin Heidelberg : Imprint: Springer.)
Journal of Economic Interaction and Coordination is a biannual journal in the vibrant and interdisciplinary field of agent-based approaches to Economics and Social Sciences. It focuses on simulating and synthesizing emergent phenomena and collective behavior in order to understand economic and social systems. Relevant topics include, but are not limited to, the following: artificial markets with heterogeneous agents, multi-agents in Economics, Experimental Economics, Econophysics, financial markets with heterogeneous agents, non-linear economic dynamics, interacting particle systems in Economics, markets as complex adaptive systems, theory and simulation of agent-based models, collective decisions, evolutionary games, market mechanisms in distributed computing systems, social and complex networks. Contributions are mostly from Economics, Physics, Computer Science and related fields and are typically based on sound theoretical models and supported by experimental validation. Survey papers are also welcome. Journal of Economic Interaction and Coordination is the official journal of the Association of Economic Science with Heterogeneous Interacting Agents. Officially cited as: J Econ Interact Coord.
Keywords: Finance; Application software; Physics; Economic theory; Economic Theory/Quantitative Economics/Mathematical Methods; Computer Appl. in Social and Behavioral Sciences; Theoretical, Mathematical and Computational Physics; Finance, general